2018
DOI: 10.1080/10286020.2018.1492565
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin: a natural pharmacologically active flavone compound with its wide range applications

Abstract: Eupatilin (5,7-dihydroxy-3',4',6-trimethoxyflavone) is a pharmacologically active flavone which has been isolated from a variety of medicinal plants. Eupatilin is known to possess various pharmacological properties such as anti-cancer, anti-oxidant, and anti-inflammatory. It is speculated that eupatilin could be subjected to structural optimization for the synthesis of derivative analogs to reinforce its efficacy, to minimize toxicity, and to optimize absorption profiles, which will ultimately lead towards pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 85 publications
0
51
0
Order By: Relevance
“…Although the causes of ALD are not well established, some studies have revealed that alcohol-induced oxidative stress, hepatotoxicity, and the complex interactions involving alcohol metabolism, liver cells, and multiple cytokines can affect the progression of ALD [26]. The antioxidant and anti-inflammatory effects of eupatilin were examined in several studies [15,17,27,28]. Recently, pharmacokinetic study also performed to demonstrate its potential benefit for diverse applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the causes of ALD are not well established, some studies have revealed that alcohol-induced oxidative stress, hepatotoxicity, and the complex interactions involving alcohol metabolism, liver cells, and multiple cytokines can affect the progression of ALD [26]. The antioxidant and anti-inflammatory effects of eupatilin were examined in several studies [15,17,27,28]. Recently, pharmacokinetic study also performed to demonstrate its potential benefit for diverse applications.…”
Section: Discussionmentioning
confidence: 99%
“…5,7-Dihydroxy-3΄,4΄,6-trimethoxyflavone (eupatilin) is a pharmacologically active flavone extracted from an Artemisia species [15]. Eupatilin is known to have several pharmacological properties, such as anti-oxidative, anti-apoptosis, and anti-inflammatory [16,17].…”
Section: Original Articlementioning
confidence: 99%
“…Infusions of génépi group plants has long been used as thermogenic agents to fatigue, indigestion, and airway infections in people . Modern medical research has revealed the pharmacological effects of eupatilin on anti‐inflammatory, anti‐ulcer, anti‐oxidative, and antineoplastic agent . In addition, eupatilin has shown anti‐diabetic, anti‐arthritis, and anti‐proliferative activity.…”
Section: Introductionmentioning
confidence: 99%
“…Eupatilin, a bioactive flavone of Artemisia asiatica Nakai (Asteraceae), has been reported to have broad properties such as anti-cancer, antioxidant, and anti-inflammatory effects [6]. In addition, Kim et al [7] reported that eupatilin has anti-allergic reactions in activated guinea pig lung mast cells, suggesting that eupatilin may be used for the treatment of inflammatory disorders associated with allergic diseases such as asthma.…”
Section: Introductionmentioning
confidence: 99%